2014
DOI: 10.1186/1756-9966-33-34
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog/Gli promotes epithelial-mesenchymal transition in lung squamous cell carcinomas

Abstract: BackgroundSquamous cell carcinomas (SCC) account for approximately 30% of non-small cell lung cancer. Investigation of the mechanism of invasion and metastasis of lung SCC will be of great help for the development of meaningful targeted therapeutics. This study is intended to understand whether the activation of Hedgehog (Hh) pathway is involved in lung SCC, and whether activated Hh signaling regulates metastasis through epithelial-mesenchymal transition (EMT) in lung SCC.MethodsTwo cohorts of patients with lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 34 publications
2
81
0
Order By: Relevance
“…Cyclopamine has been demonstrated to exert effects on numerous types of tumor, including lung, ovarian, and breast cancer (41)(42)(43). However, poor oral solubility hinders its clinical development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopamine has been demonstrated to exert effects on numerous types of tumor, including lung, ovarian, and breast cancer (41)(42)(43). However, poor oral solubility hinders its clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Hh signaling might induce EMT in pancreatic cancer (9,15). In addition, Yue et al (16) reported that Hh also promoted EMT progression in lung squamous cell carcinoma. Notably, glioma-associated oncogene-1 (Gli-1), a major Hh signaling effector, decreases levels of E-cadherin and increases those of N-cadherin (17,18), indicating that Hh signaling is important for EMT occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The identified gene sets by CDI-based method are colored yellow in pathway. Fraction score of the complex or processes, which are labeled in rectangles, is the number of the predicted genes to the number of overall genes [44][45][46][47]. For LUSC, PTPN11, PDGFC, ERBB2, HMGA1, HIPK2, and NR4A1 were also proved to be key regulators of metastatic processes in previous reports [48][49][50][51][52].…”
Section: Nsclc Metastasis Associated With Edge Biomarkersmentioning
confidence: 98%
“…On the other hand, in the other edge biomarkers for LUAD, STK36~GLI1 facilitates an important post-transcriptional control of Hedgehog (HH)/GLI signaling and also shows strong correlation with EGFR (P-value=2.317×10 −7 ). Such Hedgehog-EGFR cooperation can activate many downstream genes involved in cancer metastasis [47,55].…”
Section: Nsclc Metastasis Associated With Edge Biomarkersmentioning
confidence: 99%
“…In addition to developed resistance for Smo antagonists, mutations in Hh pathway components downstream of Smo have also been identified and cancers driven by these forms of constitutive Hh signaling would not be susceptible to treatment with Smo antagonists [11]. Finally, recent studies have identified cellular mechanisms for oncogenic Gli activation that are independent of canonical Hh/Smo signaling [12][13][14]. Taken together, these findings have led to numerous drug design efforts directly targeting Gli as a means to inhibit its ability to serve as a transcription factor that activates oncogenic signaling [3,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%